Analysis of Slopes and Their Impact on Settlements in Landslide-Prone Areas of Balikpapan City Using Geographic Information Systems (GIS) Methods - Mahardika, Hafiz Putra; Mawaddah, Najma Nur; Ningrum, Mei Vita Romadon; Azmi, Nurul (JPG (Jurnal Pendidikan Geografi), 2026)
The city of Balikpapan is dominated by hilly topography, covering approximately 85% of its area, while the remaining 15% consists of flat land. These conditions greatly influence surface runoff patterns, slope stability, land-use changes, and urban development policies, particularly those related to settlement expansion and landslide risk management. This situation has encouraged communities to build settlements in hilly areas; however, development in such locations increases the potential for landslides, especially when combined with steep slopes, high rainfall, and unstable soil conditions. This study aims to map landslide vulnerability in Balikpapan City using a GIS-based weighted overlay method. In addition to mapping vulnerability, the study also assesses the level of settlement exposure within each vulnerability class and develops spatially based mitigation strategies to support disaster risk reduction. The results of this study are expected to serve as a basis for government recommendations in landslide management and mitigation.The parameters used include soil type, land cover, slope steepness, and rainfall intensity, each weighted and scored according to its influence on landslide potential. Through the weighted overlay process, a landslide vulnerability zonation map was produced. The results show that West Balikpapan, South Balikpapan, Central Balikpapan, and North Balikpapan districts have the largest areas of high vulnerability, although the assessment covers all six districts. A total of 177,174 housing units are located within landslide-vulnerable zones, with 168,989 units in the medium vulnerability class, while the remaining 8,185 units are distributed across low and high classes. This distribution indicates that exposure is largely concentrated in medium-risk zones. Mitigation recommendations include increasing public awareness, constructing retaining walls on steep slopes, establishing evacuation routes, and installing drainage systems on steep terrain.